Lack of SCN1A mutations in familial febrile seizures - GÜNEY, AHMET İLTER (BLACKWELL PUBLISHING INC, 2002)
Purpose: Mutations in the voltage-gated sodium channel subunit gene SCN1A have been associated with febrile seizures (FSs) in autosomal dominant generalized epilepsy with febrile seizures plus (GEFS(+)) families and severe myoclonic epilepsy of infancy. The present study assessed the role of SCN1A in familial typical FSs. Methods: FS families were selected throughout a collaborative study of the Italian League Against Epilepsy. For each index case, the entire coding region of SCN1A was screened by denaturant high-performance liquid chromatography. DNA fragments showing variant chromatograms were subsequently sequenced. Results: Thirty-two FS families accounting for 91 affected individuals were ascertained. Mutational analysis detected a single coding variant (A3169G) on exon 16. The extended analysis of all family members and 78 normal controls demonstrated that A3169G did not contribute to the FS phenotype. Conclusions: Our study demonstrated that SCN1A is not frequently involved in common FSs and suggested the involvement of specific FS genes.
Keywords: febrile convulsions; idiopathic epilepsy; ion channels; genetics; mutations; GENERALIZED EPILEPSY; SODIUM-CHANNEL; GENE; CONVULSIONS; GAMMA-2-SUBUNIT; DYSFUNCTION; PLUS